2012
DOI: 10.1667/rr3120.1
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Phenotyping of Radiation and Radiation Combined Injury in Outbred Mice

Abstract: The complexity of a radionuclear event would be immense due to varying levels of radiation exposures and injuries caused by blast-associated trauma. With this scenario in mind, we developed a mouse model to mimic as closely as possible the potential consequences of radiation injury and radiation combined injury (RCI) on survival, immune system phenotype, and immune function. Using a mouse burn injury model and a 137CsCl source irradiator to induce injuries, we report that the immunological response to radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…In contrast, mortality was markedly increased in IR/MRSA mice, consistent with radiation combined injury models by other groups using burn, trauma, gram negative bacteria or enteric contents as the second injury [5][9]. To determine possible mechanisms of mortality, we performed a thorough analysis comparing NR/sham, IR/sham, NR/MRSA and IR/MRSA mice to be able to delineate which abnormalities observed were due to IR alone, MRSA alone, or a synergistic effect seen with radiation combined injury.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast, mortality was markedly increased in IR/MRSA mice, consistent with radiation combined injury models by other groups using burn, trauma, gram negative bacteria or enteric contents as the second injury [5][9]. To determine possible mechanisms of mortality, we performed a thorough analysis comparing NR/sham, IR/sham, NR/MRSA and IR/MRSA mice to be able to delineate which abnormalities observed were due to IR alone, MRSA alone, or a synergistic effect seen with radiation combined injury.…”
Section: Discussionsupporting
confidence: 85%
“…These concurrent injuries, defined as “radiation combined injuries” often worsen morbidity and mortality in animal models [5][9]. In addition to concurrent injuries, patients exposed to IR would also be at increased risk for developing infections due to increased host susceptibility to systemic infections from both endogenous and exogenous organisms [10], [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further characterization of myeloid cells demonstrated that these cells were comprised of both traditional macrophages CD11b + F4/80 + ), as well as CD11b + Gr1 + myeloid cells. These myeloid cells have been shown to increase in animal models and patients with cancer, injury and infection (5, 17, 26, 27). Cairns et al have also shown an accumulation in the periphery of CD11b + F4/80 + macrophages after burn injury (28).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances in immunity have been regarded as driving forces in radiation-induced pulmonary fibrosis (11). As a subset of CD4 þ T lymphocytes, regulatory T cells (Tregs) express the surface marker CD25 as well as the transcription factor Fox head box protein 3 (Foxp3), and they play a crucial role in the maintenance of immune-system homeostasis in the airways (12).…”
Section: Introductionmentioning
confidence: 99%